Organic Food Consumption During the COVID-19 Pandemic. A Bibliometric Analysis and Systematic Review - Romana Emilia Cramarenco; Monica Ioana Burca-Voicu; Dan-Cristian Dabija (Amfiteatru Economic, 2023)
The COVID-19 pandemic has generated multiple transformations globally, with isolation periods alternating with those marked by intense social and economic restrictions, having a major impact on economic production and distribution activities, but especially on consumer behaviour. The recent pandemic has generated a strong contraction in consumption, increasing consumers' risk aversion, and disrupting the way they purchase different foods. Consumers have shifted to sustainable consumption, preferring foods that can help them towards a balanced diet, strengthen their health, and help develop resistance to viruses. This paper aims to identify the most relevant specialised articles, published during the pandemic (2020-2023), addressing sustainable consumption of organic food. They are investigated through a bibliometric analysis, which highlights the main directions in which this international research has converged. In the investigative approach, the authors resort to applying the PRISMA methodology peculiar to this type of analysis; the references selected according to the different objective criteria chosen are subsequently analysed using the VOSviewer software. Based on the review of the literature, the paper also presents possible future research directions highlighting the opportunities for scientific capitalisation of this research topic.
Keywords: E21; L66; Q56; 330; organic food; sustainable consumption; consumer behaviour; COVID-19 pandemic.